Stent design lowers angiographic but not clinical adverse events in stenting of symptomatic intracranial stenosis – results of a single center study with 100 consecutive patients. Issue 2 (1st February 2012) - Rohde, S.; Seckinger, J.; Hähnel, S.; Ringleb, P. A.; Bendszus, M.; Hartmann, M.
Abstract : Background and aims: Comparing safety and technical success of balloon‐expandable stents and self‐expanding stents for intracranial angioplasty and stenting in medically refractory intracranial atherosclerotic disease in a single center series. Methods: Fifty‐four self‐expanding stents and 46 balloon‐expandable stents were implanted in 100 consecutive patients (mean age 64 years, 74% male) from April 2000 to September 2009. All patients had symptomatic intracranial stenosis (anterior circulation, n  = 40; posterior circulation, n  = 60), presenting with recurrent transient ischemic attack or stroke under antithrombotic treatment. Mean degree of stenosis before treatment was 83 ± 13%. We assessed safety, defined as any stroke or death during the procedure and at 30 days follow‐up, and technical success, defined as accurate delivery of the stent at the site of the target lesion. Results: Safety – periprocedural stroke or hemorrhage occurred in 11 patients treated with balloon‐expandable stent, and in 14 of the patients treated with a self‐expanding stent. One patient with a balloon‐expandable stent died because of acute vessel rupture during treatment. One balloon‐expandable stent and one self‐expanding stent patient developed a severe reperfusion hemorrhage that resulted in death. Overall, the combined stroke and death rate at 30‐day follow‐up was 25·0% (23·9% for balloon‐expandable stent group and 25·9% for the self‐expanding stent group, P  = 0·84). Technical success – intracranial angioplasty and stenting was technically successful in 96·3% of the self‐expanding stent and 89·1% of the balloon‐expandable stent patients ( P  = 0·31). Vascular complications were significantly less frequent in patients treated with a self‐expanding stent (11·1%) than with a balloon‐expandable stent (36·9%, P  = 0·002). Conclusion: Despite a high technical success, the rate of clinical adverse events at 30 days after intracranial angioplasty and stenting is high independently of the stent design. Thus, further development of intracranial stent systems and careful patient selection are mandatory.